Basic Concepts of Human Resources Development Through Education and Training - Lubis, Nasib Samsuri; Andirani, Tuti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Resources are everything that is a company's assets to achieve its goals. The company's resources can be categorized into four types of resources, such as Financial, Physical, Human and Technological Capabilities. Financial resources are one of the important elements in order to form an advanced and growing company because it is related to stocks which are the main capital in building a company and developing and continuing the company. Physical resources are resources that concern the physical support of the establishment of a company such as its fittings. Human resources is a central and important sector in order to achieve goals in a company, because with the ability of the skills of workers and the quality of human resources can move the company properly and correctly. In the improvement, development and formation of the workforce is carried out through coaching efforts, education and training. Education and training programs are designed to obtain good quality human resources and be ready to compete in the labor market.